The ventral and dorsal lateral geniculate nucleus of the rat: intracellular recordings in vitro. - Crunelli, V (1987)
1. The membrane properties and the electrotonic structure of neurones in the ventral and dorsal lateral geniculate nucleus (l.g.n.) of the rat were studied using an in vitro slice preparation. 2. Following electrophysiological characterization, horseradish peroxidase (HRP) was injected intrasomatically and the morphological features of impaled cells were characteristic of principal neurones of the rat ventral and dorsal l.g.n. 3. Neurones in the ventral l.g.n. had a higher input resistance but similar membrane time constants (tau o) and resting potentials than cells in the dorsal l.g.n. 4. Using a simple neuronal model, the electrotonic length (L) and the dendritic to somatic conductance ratio (rho) were calculated and found to be similar for cells in both divisions of the l.g.n. The mean value of L (0.7) and rho (1.5) suggest that both groups of neurones are electrotonically compact. 5. The width and after-hyperpolarization of directly evoked action potentials, but not their threshold or their amplitude, were different between cells of the ventral and dorsal l.g.n. 6. At potentials more negative than -55 mV, a slow rising and falling potential could be evoked in each neurone (n = 310) of the dorsal l.g.n. but only in three cells of the ventral l.g.n. (n = 94). The electrophysiological and pharmacological properties of this potential were identical with those of the low-threshold Ca2+-dependent potential observed in other thalamic nuclei. 7. These results indicate that some of the passive and active membrane properties of ventral and dorsal l.g.n. neurones are different. The implications of these findings for the control of the integrative capability and the response of l.g.n. neurones to visual stimulation are discussed.